The quality in the anthropological investigation - Sanmartin, Ricardo (2009)
The article deals with a very basic and inicial problem in empirical research: The quality of ethnographic data. The very first steps in empirical research are crucial for the truth and goodness of any result and conclusion but, as tutorial experience shows, many wrong attituds are unfortunately so frequent that it seems necessary some reflexive thought on vices of research as well as on qualities of good quality research. The barreness of etnographic data, unable to say something meaninful about the truthful life of social actors, is one of those vices that can be overcome and resolved if the observer learns to pay attention to otherness, complexity and specificity of culture. A good quality research springs from a sound respect for the imperious reality and otherness of actors’ culture and society, and succesfully perceives a truly relevant human problem